Pengembangan permainan tradisional tektok (tembak pletok) untuk meningkatkan motivasi belajar peserta didik SD N Sumberkepuh pada mata pelajaran PJOK - Haq, Moh Agung Izzul; Burstiando, Rizki; Yuliawan, Dhedhy (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to develop the traditional game tektok (shoot pletok) to increase the learning motivation of Sumberkepuh Elementary School students in PJOK subjects. This research uses the Research and Development (R&D) method with the ADDIE model. Data collection techniques were carried out by interviews, observation, and distributing questionnaires. Limited trials were carried out on 20 fourth grade students at SDN Sumberkepuh 5, while extensive trials were carried out on high grade students at SDN Sumberkepuh 3, SDN Sumberkepuh 4, and SDN Sumberkepuh 5. The results of this research can be concluded that this research has produced a traditional tektok game in PJOK learning. This product can be used because it has reached the standard assessment criteria of validity, practicality and effectiveness as follows: 1) Validity test results obtained 92% with very valid and usable criteria. 2) The results of the practicality test for students and teachers received an accumulative score of 90% in the very practical category. 3) The results of the effectiveness test are accumulated with a score of 97%, which means that the effectiveness test of the traditional tektok (shoot pletok) game product has very effective criteria and can increase students' learning motivation.